2012
DOI: 10.5539/ijbm.v7n4p195
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Quality of Health Care Services in the Hashemite Kingdom of Jordan

Abstract: The purpose of this study is to evaluate the quality of health care services provided in the Hashemite Kingdom of Jordan. An instrument of the quality of health service was developed in order to achieve the purpose of this study. The instrument consisted of (31) items, distributed on five dimensions: tangibles, reliability, responsiveness, assurance and empathy. The indications of validity and reliability were confirmed.The sample of this study consisted of (556) patients admitted in hospitals located in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
1
10
2
Order By: Relevance
“…The proposed model can be extended to different services industries. The study revealed different implications for Jordanian healthcare services which are supported by other studies conducted in Jordan such as (Abu kharmeh, 2012). It is necessary for hospital managers to recognize patients' needs and expectations.…”
Section: Discussionsupporting
confidence: 56%
“…The proposed model can be extended to different services industries. The study revealed different implications for Jordanian healthcare services which are supported by other studies conducted in Jordan such as (Abu kharmeh, 2012). It is necessary for hospital managers to recognize patients' needs and expectations.…”
Section: Discussionsupporting
confidence: 56%
“…Ramez 27 study ranked reliability as the highest and assurance the lowest service quality dimension. Abu Kharmeh 28 identified responsiveness as the most important dimension, and reliability as the least important dimension. Adebayo et al 29 study observed the highest service quality gap in assurance and positive gap in empathy dimensions, indicating expectations are met in this dimension among the patients attending the dental clinic.…”
Section: Discussionmentioning
confidence: 99%
“…In this plan, we need to measure and improve Service Quality (SQ) as one of the efficient and important common factors to assess the success in healthcare services (6). Due to the greater importance of SQ for both service provider and consumer, the quality of service has a critical role in designing services and marketing (7). SQ has been defined as the difference between customers' needs and what they really receive (8).…”
Section: Introductionmentioning
confidence: 99%